ANALYSIS OF EU COUNTRY INNOVATION INDICATORS AS FACTORS OF THEIR COMPETITIVE ADVANTAGES - Voytovych, Nataliya (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The results of the research and review of the literature on innovation and technology transfer are presented. Innovation is a leading force in competitiveness, growth, profitability, and the creation of sustainable values, as it is well known that competitive advantage is so desirable by any organization and country operating in a highly competitive environment. In this article, we have tried to highlight innovation through the following: identification of innovation and technology transfer; their features; comparative analysis of EU countries according to the system of innovation indicators. Statistical indicators are an excellent support for this study. Together with the knowledge that influences statistics, they provide an opportunity for in-depth and systematic analysis of the situation, causes and trends. The research materials in this article contain secondary sources of information, such as Eurostat data, Statista, business reports of the European Parliament, newsletters, and publications. The study period covered 2014-2019 and data for 30 countries. The article uses a qualitative method – indicators on the ground to assess technology transfer and the level of innovation in the economy of the European Union. We have selected the main indicators that characterize the transfer of technology and innovation by 9 parameters, namely: R&D costs of business; non-R&D innovation costs; innovative SMEs collaborating with others; patent applications; patent applications in solving social problems; export of medium and high-tech products; export of knowledge-intensive services; sale of novelties on the market and novelties for innovations; licensed and patent receipts from abroad. The study of the internal structure of the set of objects based on the values of the selected indicators was carried out using cluster analysis methods, where countries are divided into two clusters. The analysis showed that countries with developed economies have sufficient competitive advantages. And countries in the third group of moderate innovators have only one competitive advantage. All other indicators need to be improved, creating additional competitive advantages.